2013
DOI: 10.1111/dmcn.12209
|View full text |Cite
|
Sign up to set email alerts
|

Two types of exercise‐induced neuroplasticity in congenital hemiparesis: a transcranial magnetic stimulation, functional MRI, and magnetoencephalography study

Abstract: ABBREVIATIONS CIMTprojections from the contralesional hemisphere, which can enable the contralesional hemisphere to exert motor control over the paretic hand. In contrast to the primary motor representation (M1), the primary somatosensory representation (S1) of the paretic hand always remains in the lesioned hemisphere. Here, we report on differences in exerciseinduced neuroplasticity between individuals with such ipsilateral motor projections (ipsi) and individuals with early unilateral lesions but 'healthy' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
117
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(124 citation statements)
references
References 41 publications
3
117
3
1
Order By: Relevance
“…In addition, changes in motor-evoked potentials of the affected hand were quantified by transcranial magnetic stimulation as an alternative treatment response metric. 20 In recent years, fNIRS has been increasingly shown as a viable alternative neuroimaging modality to fMRI for monitoring brain activation. 21,22 FNIRS detects changes in near-infrared light absorption caused by changes in the concentration of oxyhemoglobin (ΔHbO) and deoxyhemoglobin (ΔHb) resulting from neuronal activity, known as neurovascular coupling.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, changes in motor-evoked potentials of the affected hand were quantified by transcranial magnetic stimulation as an alternative treatment response metric. 20 In recent years, fNIRS has been increasingly shown as a viable alternative neuroimaging modality to fMRI for monitoring brain activation. 21,22 FNIRS detects changes in near-infrared light absorption caused by changes in the concentration of oxyhemoglobin (ΔHbO) and deoxyhemoglobin (ΔHb) resulting from neuronal activity, known as neurovascular coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Children's mastery motivation is a force that energizes, directs, and sustains goal-directed behavior 2 and is a predictor of later functioning. 3 For children with developmental disabilities, mastery motivation is also a predictor of later performance of daily activities and academic achievement. 4 The book 'From Neurons to Neighborhoods' identifies mastery motivation as a key developmental concept, which should be assessed as part of a child's evaluation.…”
mentioning
confidence: 99%
“…4 The book 'From Neurons to Neighborhoods' identifies mastery motivation as a key developmental concept, which should be assessed as part of a child's evaluation. 3 The article by Miller et al 1 demonstrates that inadequate parenting relates cross-sectionally to lower mastery motivation for school-aged children with congenital hemiplegia, using the parental report Dimensions of Mastery Questionnaire (DMQ). With cross-sectional studies it is less possible to know whether maternal behavior has an effect on children's motivation than with a longitudinal study design.…”
mentioning
confidence: 99%
“…101 In the third study, an associated analysis showed bilateral activation of S1-M1 in adolescents with corticospinal projections ipsilateral to the impaired hand; the balance of this activation shifted towards the impaired hemisphere after training. 69 In the same study, CIMT increased TMS-evoked MEPs in the primary descending corticospinal connection to the impaired hand, but not to the unimpaired (constrained) hand, in children with UCP, regardless of whether the impaired hand was controlled by the contralateral or ipsilateral motor cortex. MEG data that was acquired at the same time also found that somatosensory-evoked magnetic fields increased marginally in both groups after mCIMT.…”
Section: Multimodal Studies and Cimtmentioning
confidence: 86%
“…Three related studies of children with UCP have used a multimodal approach to investigate brain changes that occur in response to mCIMT. 68,69,101 These reports, which used data from two studies with overlapping participants, used fMRI to assess how brain activation changed when a ball-squeezing task was performed with the impaired hand. After exclusion of scans that were influenced by confounding factors, the first of these studies found no activation changes in two participants, and increased bilateral activation of the hand knob of the sensorimotor cortices in one individual aged 16 years with UCP.…”
Section: Multimodal Studies and Cimtmentioning
confidence: 99%